Pengaruh Citra Merek Dan Harga Terhadap Keputusan Pembelian Smart Phone Vivo Studi Kasus Pada Mahasiswi Umsu Fakultas Ekonomi Dan Bisnis - Novi Aisha (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2020)
The aim of the study was to determine and analyze the partial effect of brand image on the purchase decision of Vivo smartphone products studied by FEB UMSU students, to determine and analyze the partial effect of price on purchasing decisions of Vivo smartphone products studied by FEB UMSU students, to determine and analyze the effect of Simultaneous brand image and price on purchasing decisions for Vivo smartphone products studied by FEB UMSU students. The research approach used in this research is associative and quantitative. The number of research samples is 100 students from the Faculty of Economics and Business, Muhammadiyah University of North Sumatra. Based on the results of the partial t-test, there is a significant influence between the Brand Image variables on Purchase Decisions for Students of the Faculty of Economics and Business UMSU. Based on the results of the partial test, there is a significant influence between the price variable on purchasing decisions for students of the UMSU Faculty of Economics and Business. Based on the simultaneous F test, there is a significant effect between the Brand Image and Price variables on Purchase Decisions for Students of the Faculty of Economics and Business UMSU.